Dampak Peranan Kompetensi Pedagogik Guru dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPS dI SMPN 3 Pandeglang - Cahya, Nilam; Kuntari, Septi (Lembaga Yasin AlSys, 2022)
The objectives of this study are 1) to explain the pedagogic competence of teachers. 2) student learning outcomes in social studies subjects. 3) to explain the impact of the role of teacher pedagogic competence in improving student learning outcomes in social studies subjects. This research uses a qualitative approach. The type of research used is a case study. The subjects in this study were students, homeroom teachers, school principals. Data collection techniques are observation, interviews, and documentation techniques. Based on the results of the analysis, 1) the pedagogic competence of the social studies teacher at SMPN 3 Pandeglang is good because the social studies teacher is professionally certified. 2) student learning outcomes of SMPN 3 Pandeglang IPS have developed since the teacher applied pedagogic competence to the learning process. 3) Thus it can be seen that pedagogic competence has a very important role in teaching and learning activities, namely making it easier for teachers to convey material to students and teachers can apply various learning strategies so as to create fun teaching and learning activities.